An evaluation of Islamic moral teaching for students of Madrasah Aliyah Negeri (MAN) - Siti Amanah; Haryanto Haryanto (REID (Research and Evaluation in Education), 2018)
This research is aimed at evaluating: the preparation, implementation, and outcome of the moral teaching program using Stake Countenance evaluation model (antecedent, implementation, and outcome). The study was conducted at Madrasah Aliyah Negeri (MAN) Cilacap, MAN Kroya, and MAN Majenang. The subjects were the principals, teachers of Aqidah Akhlak, chairpersons of the Madrasah Committee, and 276 grade XII students. Interview, observation, questionnaire, and documentation were used as data collection techniques. The data analysis method used was the quantitative-qualitative descriptive analysis. The result of the evaluation shows that: (1) the preparation of the moral teaching is in ‘good’ category; (2) the implementation of moral teaching in terms of time and methods is in ‘good’ category, but the model of moral judgments used is not in ‘good’ category; (3) the result of moral teaching in the madrasah and outside the madrasah as a whole is in ‘good’ category. Thus, Islamic moral teaching evaluation of MAN in Cilacap Regency viewed from the preparation, implementation, and the result is in accordance with the evaluation criteria. In addition, there is a need for further action to examine the effectiveness of moral teaching in madrasahs.